Wet and wild! - Krulik, Nancy E.; Blecha, Aaron (New York : Grosset & Dunlap, 2011)
Fourth-grader George gets help from his friend Alex in trying to control the magic burps that take control and cause him to misbehave in funny ways, but when the class bully celebrates his birthday at a water park, anything can happen.
540
Accelerated Reader AR
Keywords: Birthdays -- Juvenile fiction; Amusement parks -- Juvenile fiction; Belching -- Juvenile fiction; Magic -- Juvenile fiction; Human behavior -- Juvenile fiction